Steriphoma menispermifolia: A new species of Capparaceae from Colombia (Revista Científica Ciencias Naturales y Ambientales, 2016)
Steriphoma menispermifolia (Capparaceae) a new species of liana from the lowlands of the Department of Santander, Colombia, is here described and illustrated. The subcordate to strongly cordate leaf bases and the petals reflexed at anthesis characterize the new species. A key for identification to the species of Steriphoma is provided.
Keywords: Capparaceae; Colombia; endemic; new species; Steriphoma menispermifolia